The role of individuals in the resilience of local medical systems based on the use of medicinal plants – a hypothesis - Ferreira Júnior, Washington Soares; Santoro, Flávia Rosa; Nascimento, André Borba; Ladio, Ana Haydée; Albuquerque, Ulysses Paulino (Ethnobiology and Conservation, 2013)
Some studies in the field of ethnobiology investigate the knowledge and use of biological resources, especially medicinal plants, to infer the resilience of local medical systems. However, little is known about the resilience of such systems in the context of the distribution of knowledge among individuals in the studied communities. For example, although a medical system is formed by a diverse set of species, the distribution of knowledge may be limited to a small number of individuals, which reduces its flexibility and does not favor its resilience. Thus, this manuscript proposes the hypothesis that the medical system appears resilient when assessing the knowledge of the individuals who compose the system. The knowledge of medicinal plants for the treatment of therapeutic targets among the individuals is used as an example. Additionally, predictions are made and a methodological protocol is described to test the hypothesis by a simple analysis.